Effect of N-acetyl cysteine on the concentrations of thiols in plasma, bronchoalveolar lavage fluid, and lung tissue. Issue 7 (July 1994) - Bridgeman, M M; Marsden, M; Selby, C; Morrison, D; MacNee, W
Abstract : BACKGROUND–Oxidant/antioxidant imbalance may occur in the lungs of patients with chronic obstructive pulmonary disease (COPD). Glutathione is an important extracellular and intracellular thiol oxidant in the lungs. These studies were carried out to determine the effect of N-acetyl cysteine on thiol concentrations in plasma, bronchoalveolar lavage fluid, and lung tissue. METHODS–Studies were carried out on normal subjects, patients with COPD, and those undergoing lung resection. In the first study N-acetyl cysteine was given to three groups; healthy subjects (600 mg once daily by mouth) and two groups of patients with COPD. In the first group of patients with COPD the dose was 600 mg once daily and in the second 600 mg thrice daily, all for five days. The latter dosage regimen was also given to six patients before bronchoscopy and to 11 patients before lung resection. Lung glutathione (GSH) levels in bronchoalveolar lavage fluid or lung tissue were compared with the same numbers of patients who did not receive N-acetyl cysteine. RESULTS–N-acetyl cysteine was detected in plasma after a single 600 mg dose in normal subjects and patients with COPD up to 1.5 hours after the drug was given. Plasma cysteine concentrations increased in normal subjects on both days 1 and 5, and in patients with COPD on day 5. Glutathione concentrations in plasma increased on day 1 in normal subjects but not in patients with COPD given 600 mg N-acetyl cysteine daily. With the higher dose of 600 mg thrice daily, however, there was a sustained elevation of GSH concentrations in plasma in patients with COPD. In patients undergoing routine diagnostic bronchoscopy and bronchoalveolar lavage those who were given N-acetyl cysteine (600 mg) thrice daily for five days had higher concentrations of cysteine in the plasma, but no significant differences in cysteine concentrations in bronchoalveolar lavage or epithelial lining fluid compared with a control group; nor were there any differences in reduced glutathione concentrations in plasma, bronchoalveolar lavage or epithelial lining fluids between the control and treated groups. Moreover, in patients undergoing lung resection those treated with N-acetyl cysteine (600 mg thrice daily for five days) had similar concentrations of cysteine and glutathione in both plasma and lung tissue when compared with a control untreated group. CONCLUSIONS–These data suggest that, even when given in high oral doses, N-acetyl cysteine does not produce a sustained increase in glutathione levels sufficient to increase the antioxidant capacity of the lungs.